High Risk of Pulmonary Embolism and Deep Venous Thrombosis but Not of Stroke in Granulomatosis With Polyangiitis (Wegener's). Issue 12 (December 2014) - Faurschou, Mikkel; Obel, Niels; Baslund, Bo
<x xml:space="preserve">Abstract</x> Objective To assess the incidence of stroke, pulmonary embolism (PE), and deep venous thrombosis (DVT) in granulomatosis with polyangiitis (Wegener's) (GPA). Methods Patients diagnosed with GPA at a Danish tertiary care center during 1993–2011 were identified (n = 180). Each patient was matched with 19 population controls (n = 3, 420). Information on hospitalizations for stroke, PE, and DVT was obtained from the Danish National Hospital Register. The occurrence of vascular events in the GPA cohort was compared with that in the control group by calculation of incidence rate ratios (IRRs). Results The median duration of followup was 7.2 years (interquartile range 3.1–11.7 years) in the GPA cohort. Within the first 2 years following the diagnosis of vasculitis, the incidences of PE and DVT were substantially increased among the patients (IRR 25.7 [95% confidence interval (95% CI) 6.9–96] for PE and IRR 20.2 [95% CI 5.1–81] for DVT). The incidence of stroke was not increased during this time interval (IRR 1.4 [95% CI 0.3–5.7]). From 2 years after GPA diagnosis, an increased incidence was found for DVT (IRR 4.5 [95% CI 1.7–11.8]) but not for PE (IRR 1.3 [95% CI 0.2–9.6]) or stroke (IRR 1.4 [95% CI 0.6–3.3]). In the GPA cohort, 70% of the vascular events occurred during phases with active vasculitis. Conclusion The present study confirms that GPA patients have a markedly increased risk of venous thromboembolism. We did not observe an increased risk of stroke in our cohort. Thus, our observations demonstrate a differential impact of GPA and/or its treatment on the risk of various vascular events.